Foodborne Illness outbreak in Callao, Peru Case reports - Cassa-Loaiza, William (2023)
Foodborne diseases (FBD) represent an impact on public health, since they are responsible for the increase in mortality and morbidity rates, generating greater negative effects in low and middle-income countries. This manuscript reports a FBD outbreak in the Callao region, Peru, which affected 33 people with persistent gastrointestinal symptoms. These cases call for epidemiological surveillance in health centers in order to determine the pathogen and generate an efficient treatment.